Enhancing Elementary Students’ Understanding of Pancasila Values: Exploring MANILA, a Canva-Based Interactive Learning Tool - Musfirotun, Rika; Widodo, Susilo Tri (International Journal of Elementary Education, 2024)
Teachers played very important role in learning where teachers had to be able to provide learning that were adapted to technological development. Teachers had to be able to provide media where students could understand the material as a whole and continued so that the progress of learning media such as interactive media “MANILA” (Interactive media of Pancasila values) was needed. This study aimed to produce Canva-assisted learning media in the subject of Pancasila Education, the material of Pancasila values in grade V SD which was tested for feasibility and effectiveness and was able to improve student learning outcomes. This research was a research and development with the Borg and Gall model which was limited to the fourth stage. The research subjects consisted of: 1 material expert, 1 media expert, 1 class teacher, 6 students for small-scale trials, and 15 students for large-scale trials. Data collection techniques used interviews, validation sheets, response questionnaires, and tests. The media was also declared effective which could be seen from the pretest and posttest results and the T-test results, namely T (15) = 4.06, p < 0.05. Therefore, the development of interactive media “MANILA” assisted by Canva was concluded to be very feasible, practical, and effective in improving student learning outcomes.